Impact of ironman triathlon on oxidative stress Parameters - José Claudio Fonseca Moreira; Magnus Benetti; Luciano Acordi da Silva; Mariana Leivas Müller Hoff; Cleber Aurino Pinho; Débora da Luz Scheffer; Ricardo Aurino Pinho (Universidade Federal de Santa Catarina, 2012)
Several studies have investigated the biochemical response changes that take place in Ironman triathletes, but there are few data on oxidative stress changes. The objective of this study was to investigate oxidative stress parameters in triathletes after an Ironman event. The sample consisted of eighteen male triathletes, with a mean age of 34.5 ± 2.15 years, weight 69.3 ± 1.9 kg, and height 1.71 ± 0.18 m. The Ironman triathlon consists of a 3.8-km swim, a 180-km bicycle ride, and a 42.2-km (marathon) run. Before the competition and immediately after its conclusion, 10-mL blood samples were collected, centrifuged and frozen at -80ºC for subsequent analysis. Total antioxidant capacity, lipid peroxidation, protein carbonylation, and total thiol content were measured. The results showed a significant increase in all markers after the event (p<0.05) in relation to the pre-event period, which conclusively shows that the Ironman triathlon induces significant changes oxidative stress markers in athletes and that antioxidant supplementation would be important to reverse these effects.